Ubiquitination as a Key Regulator of Endosomal Signaling by GPCRs - Burton, Jeremy C.; Grimsey, Neil J. (Frontiers in Cell and Developmental Biology, 2019)
G protein-coupled receptors (GPCRs) represent the largest family of therapeutic targets for FDA approved drugs. Therefore, understanding the molecular regulation of their signaling pathways is of paramount importance. Similarly, the mitogen activated protein kinase (MAPK) p38 is a critical mediator of proinflammatory disease. Yet despite decades of intense investigation, therapeutically viable inhibitors have struggled to make it into the clinic. New studies describing the regulation and activation of a GPCR dependent atypical p38 signaling pathway represents a novel therapeutic avenue to the treatment of many proinflammatory disorders. These recent studies have defined how thrombin and ADP can induce Src dependent activation of the E3 ubiquitin ligase NEDD4-2. Src dependent phosphorylation of a 2,3-linker peptide releases NEDD4-2 auto-inhibition and triggers the induction of proinflammatory atypical p38 signaling from the endosome. Activation of the atypical p38 pathway requires the direct interaction between an adaptor protein TAB1 and p38, that bypasses the requirement for the classical MKK3/6 dependent activation of p38. Therefore, providing a mechanism to specifically block proinflammatory GPCR atypical p38 activation while leaving basic p38 activity intact. Critically, new studies demonstrated that disruption of the TAB1-p38 interface is a druggable target, that would enable the selective inhibition of proinflammatory p38 signaling and ischemic injury. Atypical p38 signaling is linked to multiple clinically relevant pathologies including inflammation, cardiotoxicity, myocardial ischemia and ischemia reperfusion injury. Therefore, GPCR induced endosomal p38 signaling represents a novel understudied branch of proinflammatory p38 signaling and an ideal potential therapeutic target that warrants further investigation.